Placenta accreta is an independent risk factor for late pre-term birth and perinatal mortality. (August 2015) - Vinograd, Adi; Wainstock, Tamar; Mazor, Moshe; Beer-Weisel, Ruthy; Klaitman, Vered; Dukler, Doron; Hamou, Batel; Novack, Lena; Ben-Shalom Tirosh, Neta; Vinograd, Ofir; Erez, Offer
Abstract Objective: This study is aimed to identify the risk factors for the development of placenta accreta (PA) and characterize its effect on maternal and perinatal outcomes. Study design: This population-based retrospective cohort study included all deliveries at our medical center during the study period. Those with placenta accreta (n = 551) comprised the study group, while the rest of the deliveries (n = 239 089) served as a comparison group. Results: The prevalence of placenta accerta is 0.2%. Women with this complication had higher rates of ≥2 previous CS (p < 0.001), recurrent abortions (p = 0.03), and previous placenta accreta [p < 0.001]. The rates of placenta previa and peripartum hemorrhage necessitating blood transfusion were higher in women with placenta accreta than in the comparison group. PTB before 34 and 37 weeks of gestation was more common among women with placenta accreta (p < 0.01), as was the rate of perinatal mortality (p < 0.001). Placenta accreta was an independent risk factor for perinatal mortality (adj. OR 8.2; 95% CI 6.4–10.4, p < 0.001) and late PTB (adj. OR 1.4; 95% CI 1.1–1.7, p = 0.002). Conclusion: Placenta accreta is an independent risk factor for late PTB and perinatal mortality.